2020
DOI: 10.1093/narcan/zcaa008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of structure-specific endonucleases EEPD1 and Metnase in replication stress responses

Abstract: Accurate DNA replication and segregation are critical for maintaining genome integrity and suppressing cancer. Metnase and EEPD1 are DNA damage response (DDR) proteins frequently dysregulated in cancer and implicated in cancer etiology and tumor response to genotoxic chemo- and radiotherapy. Here, we examine the DDR in human cell lines with CRISPR/Cas9 knockout of Metnase or EEPD1. The knockout cell lines exhibit slightly slower growth rates, significant hypersensitivity to replication stress, increased genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…(C) RAD52 also recognizes and repairs stalled replication forks via break-induced replication (BIR). The structure is cleaved by the endonuclease complex MUS81 and processed by EEPD1 ( Kim et al, 2017 ; Sharma et al, 2020 ). Bound to the one-ended DNA break, RAD52 invades the dsDNA to form a D-loop.…”
Section: Introductionmentioning
confidence: 99%
“…(C) RAD52 also recognizes and repairs stalled replication forks via break-induced replication (BIR). The structure is cleaved by the endonuclease complex MUS81 and processed by EEPD1 ( Kim et al, 2017 ; Sharma et al, 2020 ). Bound to the one-ended DNA break, RAD52 invades the dsDNA to form a D-loop.…”
Section: Introductionmentioning
confidence: 99%
“…Template switching uses sister chromatids to bypass blocking lesions and is generally error-free ( Figure 2A ), but poses risks of genome rearrangement from replisome switching to non-sister templates ( Lehmann et al, 2020 ). Two additional restart pathways are fork reversal to a Holliday junction-like structure followed by fork restoration, and fork cleavage by structure-specific nucleases including the 3′ nuclease MUS81 (with EME2) ( Pepe and West, 2014 ) and the 5’ nuclease EEPD1 ( Wu et al, 2015 ; Sharma et al, 2020 ) ( Figure 2B ). Metnase is a structure-specific nuclease that promotes fork restart, but Metnase does not cleave stalled forks and instead may process flaps that arise later ( Sharma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two additional restart pathways are fork reversal to a Holliday junction-like structure followed by fork restoration, and fork cleavage by structure-specific nucleases including the 3′ nuclease MUS81 (with EME2) ( Pepe and West, 2014 ) and the 5’ nuclease EEPD1 ( Wu et al, 2015 ; Sharma et al, 2020 ) ( Figure 2B ). Metnase is a structure-specific nuclease that promotes fork restart, but Metnase does not cleave stalled forks and instead may process flaps that arise later ( Sharma et al, 2020 ). SLX1-SLX4 is another structure-specific nuclease that resolves branched replication intermediates, and although it cleaves many types of branched structures including replication fork structures in vitro , direct evidence that it cleaves stalled forks in vivo is lacking ( Falquet and Rass, 2019 ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SETMAR has also been proposed to act in DNA replication and cell cycle regulation (Figure 4A). Knockdown, knockout, or overexpression of SETMAR has more or less of an effect on cell cycle depending on the cell type, with generally a higher SETMAR expression correlating with an increased growth rate [16,19,21,44,61]. While phosphorylation of SETMAR on the Ser508 residue by Chk1 is associated with DNA damage repair via NHEJ, the unphosphorylated form of SETMAR is involved in the response to replication stress [47].…”
Section: Cellular Roles and Functionmentioning
confidence: 99%
“…The endonuclease activity of SETMAR is thought to be involved in the cleavage of branched DNA structures resulting from stress replication forks, producing DSBs that can be resolved by DNA damage repair pathways and thus allowing the restart of replication forks [16,40,62,63]. A recent work has proposed that SETMAR role in the response to replication stress was mediated by the dimethylation of H3K36 at stalled replication forks, facilitating the recruitment of DNA repair factors, rather than a cleavage of stalled forks via SETMAR endonuclease activity [61]. It has been recently suggested that SETMAR could bind to 12 bp motifs that are enriched in the regions of replication origins but more work is required to determine whether SETMAR binding is occurring simultaneously to DNA replication and whether SETMAR binding plays a role in DNA replication [34].…”
Section: Cellular Roles and Functionmentioning
confidence: 99%